The Return of Practice to Higher Education: Resolution of a Paradox - Joseph A. Raelin (The Journal of General Education, 2007)
Although academic provision has become associated with professional education, knowledge is delivered through standard classroom methodology associated with liberal arts education. Elsewhere, a "practice turn" has elevated experience as a basis for knowledge. This article shows how practice became detached from theory and how through praxis they can be reintegrated.
Keywords: I20; I21; I28; H52; I29; L30; L32; M53; O15; 330; Praxis; Reflective practice; Epistemology of Practice; Practice-based education; Critical pedagogy; Facilitation; Action learning